2018
DOI: 10.1371/journal.pone.0200102
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of non-proteolytic Clostridium botulinum type E in low-acid foods and phosphate buffer by heat and pressure

Abstract: The effect of high pressure thermal (HPT) treatments on the inactivation of spores of non-proteolytic type E Clostridium botulinum TMW 2.990 was investigated at high pressures (300 to 600 MPa) and elevated temperatures (80 to 100 °C) in four low-acid foods (steamed sole, green peas with ham, vegetable soup, braised veal) and imidazole phosphate buffer (IPB). In addition, corresponding conventional thermal treatments at ambient pressure were performed to expose possible synergisms of pressure and temperature on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 38 publications
1
9
0
Order By: Relevance
“…High-temperature processing in the food industry is the most effective method for inactivation of C. botulinum spores and the neurotoxin, but often compromises nutritional and sensory qualities of food products 4 . There is a growing interest in development of novel methods alternative to thermal process to control the botulism hazard 5 , 6 .…”
Section: Introductionmentioning
confidence: 99%
“…High-temperature processing in the food industry is the most effective method for inactivation of C. botulinum spores and the neurotoxin, but often compromises nutritional and sensory qualities of food products 4 . There is a growing interest in development of novel methods alternative to thermal process to control the botulism hazard 5 , 6 .…”
Section: Introductionmentioning
confidence: 99%
“…In recent studies with proteolytic (types B) and nonproteolytic (type E) C. botulinum strains in food model systems and different types of real foods, spore stabilization by HHP against high temperature inactivation could be confirmed, namely for type B strains. It was demonstrated for C. botulinum type B that, at a given temperature (100, 110, and 120 • C), spore inactivation was increased when pressure was reduced, for example, from 600 to 300 MPa (Maier et al, 2018). Such fundamental differences given, it is unlikely that true surrogates for Clostridium spores for the purpose of evaluating the effectiveness of HPT processes can be found within Bacillus species.…”
Section: Hpt Processes For Endospore Inactivationmentioning
confidence: 99%
“…Maier et al. (2018) have suggested that storage temperatures below 3°C can be considered (for low‐acid chilled storage products) as a safety limitation for chilled meals.…”
Section: Pasteurizationmentioning
confidence: 99%
“…The results of these various studies emphasize the need for temperature control during storage for the microbial safety of low-acid pasteurized products. Maier et al (2018) have suggested that storage temperatures below 3 • C can be considered (for low-acid chilled storage products) as a safety limitation for chilled meals.…”
Section: Nonproteolytic C Botulinummentioning
confidence: 99%